Seize the time : towards OECS political union - Demas, William G. ([s.n.] St MichaelBB, 1987)
Reviews attempts at West Indian cooperation and unity since the collapse of the federation in 1962 and argues case for wider political union in the West Indies. Outlines the reasons why it is necessary to start with OECS political unity. Discusses three forms of political unity for the OECS. Comments on questions and doubts concerning political union. Emphasizes fact thatOECS political union must be set firmly within framework of Caribbean Community. Outlines interim steps that should be taken before political union. Expresses view that political union by itself is not enough but should be accompanied by sound development policies.